Research ethics - Aşkın Yaşar; Adnan Ataç (Eurasian Journal of Veterinary Sciences)
Honesty ıs oî central importance in scientific researches. Principles of "do no harm, beneficence, justice, privacy. respect tor autonomy and informed consent" are also important in research ethics. There may be errors during the phases of subject selection, collection and processing of data, evaluation and assessment of findings and announcemeni of resuits in any scientific research. If rt was made purposely by the researcher, this is scientific fraud. Publication brings about some special ethical problems. Plagiarism, dual publication, undeserved claims of co-authoring, omission of coauthors and publication by dividing into parts are remembered fist in this context. The condition for conducting ethically problem-free research is that, the researcher must have good ethical sense Good ethical sense is the contemporary universal norm of ethics. One needs to be educated in research ethics, along with scientific research methodology in order to attain this level.